Delimitation of connectivity corridors between geographically protected urban-rural areas of the Guayaquil canton - Juan Carlos Torres Espinoza; Alina Delgado Bohórquez (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca)
Ecological corridors, as components of green space at the urban and rural level, significantly reduce the effects of high urban compactness. The built space exerts pressure on the territory and the green space is a means of decompression. The purpose of this research is to delimit the connectivity of ecological corridors between protected areas of Guayaquil, through the connection of ecosystems, linking the rural periphery with the urban core, for the sustainability of the urban green structure. To standardize the components the landscape matrix criterion was used, where the corridors link elements of protected areas with flexible land use connections. Thus, to determine the similarity of ecosystems, the similarity index was used as a statistical sampling technique. The results allowed us to identify ecological corridors that can be part of territorial strategic planning.